ANALISIS MODEL CIPP PELAYANAN PUBLIK PADA PROGRAM SALAM IND PROBO DI PENGADILAN AGAMA KOTA PROBOLINGGO - Nareswari Ratnaduhita; Veronica Sri Astuti Nawangsih; Mastina Maksin (The Indonesian Journal of Public Administration (IJPA), 2026)
This study evaluates the implementation of the SALAM IND PROBO program (Satu Loket bagi Semua Layanan Terintegrasi Digital Pengadilan Agama Probolinggo) at the Religious Court of Probolinggo City using the CIPP evaluation model (Context, Input, Process, Product) by Stufflebeam and Coryn (2014). The research uses a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews, participatory observation, and documentation. Findings show all CIPP components are fulfilled: (1) Context - the program addresses real public need with strong regulatory grounding; (2) Input - HR with multi-functional competency, adequate facilities, and SOPs are ready; (3) Process - services run smoothly per SOP with real-time digital monitoring; (4) Product - queuing is resolved, service speed improves, user satisfaction is high, and the program is a reference model for other religious courts in East Java. Supporting factors include leadership commitment, HR competency, digital technology, stakeholder support, and regulatory foundation. Inhibiting factors include limited budget, dependency on central E-Court, low digital literacy among users, volume peaks, and lack of integration with the Employee Performance Assessment (SKP) system.